ASSOCIATION OF SCULPTRA WITH MICROFOCUSED ULTRASOUND FOR FACIAL REJUVENATION - Sampaio Lobo, Bárbara; Regina Veronezi, Lauscea; Vivianne Nogueira, Márcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
With the increasing demand for an improvement in the appearance of the skin, technologies have advanced more and more each day, providing excellent visible and lasting aesthetic results in facial rejuvenation. A procedure that is currently in great demand and has proven to be effective is poly-L-lactic acid - Sculptra, an injectable collagen bio-stimulator that offers a non-surgical alternative with minimally invasive techniques that promises to improve and consequently delay skin aging. Another device that offers non-invasive therapy, indicated for facial lifting, sagging treatment and reduction of localized adipose tissue is the Microfocused Ultrasound – Ultraformer III. The work briefly addressed skin aging for a better explanation and aims to evaluate the effectiveness of the association of poly-L-lactic acid – Sculptra with Microfocused Ultrasound – Ultraformer III in a case study with two applications over a period of 60 days. Each of these biostimulators mentioned has certain attributes, providing an improvement in the appearance and characteristics of aging. In view of this, the sum of the two techniques demonstrates positive results according to stereographic analysis with the 3D Vectra H2 software and appropriate according to the anamnesis and problems presented by the patient.